Pregnancy-Related Immune Changes and Demyelinating Diseases of the Central Nervous System - Qiu, Ke; He, Qiang; Chen, Xiqian; Liu, Hui; Deng, Shuwen; Lu, Wei (Frontiers in Neurology, 2019)
Demyelinating diseases of the central nervous system comprise a heterogeneous group of autoimmune disorders characterized by myelin loss with relative sparing of axons occurring on a background of inflammation. Some of the most common demyelinating diseases are multiple sclerosis, acute disseminated encephalomyelitis, and neuromyelitis optica spectrum disorders. Besides showing clinical, radiological, and histopathological features that complicate their diagnosis, demyelinating diseases often involve different immunological processes that produce distinct inflammatory patterns. Evidence of demyelination diseases derives mostly from animal studies of experimental autoimmune encephalomyelitis (EAE), a model that relies on direct antibody–antigen interactions induced by encephalitogenic T cells. Pregnancy is characterized by non-self-recognition, immunomodulatory changes and an altered Th1/Th2 balance, generally considered a Th2-type immunological state that protects the mother from infections. During pregnancy, the immune response of patients with autoimmune disease complicated with pregnancy is different. Immune tolerance in pregnancy may affect the course of some diseases, which may reach remission or be exacerbated. In this review, we summarize current knowledge on the immune status during pregnancy and discuss the relationship between pregnancy-related immune changes and demyelinating diseases of the central nervous system.